Effects of ocean acidification and warming on microzooplankton communities - Horn, Henriette Gesine (2016)
Among the environmental stressors affecting the oceans, warming and acidification have been identified as two of the most important ones. Currently, the understanding of the effects of the two stressors on plankton communities forming the base of the food web is still incomplete. Data availability for long-term effects, interactions effects of the two stressors and effects on a community level is limited, especially for microzooplankton. The aim of this work was to investigate the effects of warming and high CO2 on microzooplankton on a community level. The results showed that a stronger effect of warming than of elevated CO2 can be expected for coastal microzooplankton communities with respect to realistic IPCC end-of-century scenarios. As previously suggested, indirect effects of high CO2 due to changes in the phytoplankton community composition and food quality were found to be more important than direct ones. Most likely, this can be attributed to the high tolerance of estuarine plankton communities to fluctuations in pCO2 occurring already today. In contrast, warming can be expected to directly affect microzooplankton in terms of higher growth and grazing rates, thus strengthening the coupling with phytoplankton. However, the interactions of warming and acidification were shown to be additionally affected by nutrient concentrations. Overall, the results highlight the significance of mesocosm studies at the community level under close-to-natural conditions including trophic interactions when assessing the effects of climate change. Moreover, they emphasize the importance of multiple-stressor experiments conducted during different seasons. Innerhalb der Umweltfaktoren, von denen Auswirkungen auf die Meere zu erwarten sind, gehören Erwärmung und Versauerung zu den beiden wichtigsten. Zur Zeit ist das Verständnis der Effekte dieser beiden Stressfaktoren auf die Planktongemeinschaften an der Basis des Nahrungsnetzes jedoch noch immer lückenhaft. Zudem ist die Datenverfügbarkeit in Bezug auf Langzeitwirkungen, ...